Pengaruh Green Investment dan Tata Kelola terhadap Nilai Perusahaan - Lisandri Lisandri; Akhmad Yafiz Syam; Gemi Ruwanti; Saifhul Anuar Syahdan; Riswan Yudhi Fahrianta (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to investigate the impact of integrating green investment (GI) and good corporate governance (GCG) practices on firm value among companies listed in the SRI-KEHATI Index on the Indonesia Stock Exchange during the 2020–2024 period. Using a panel data regression approach, the study seeks to address the literature gap concerning the synergy between sustainability initiatives and effective governance in value creation, particularly within the context of emerging markets. The results indicate that, individually, green investment has a positive and statistically significant effect on firm value, while GCG exerts a positive but statistically insignificant effect. However, when considered simultaneously or integratively, green investment and GCG jointly have a positive and significant influence on firm value. These findings suggest that the combination of sustainable investment and sound governance enhances market perceptions of firms and contributes to long-term value creation